Mathematical modeling of a continuous solution polymerization reactor: case-study MMA polymerization - Brahim Benyahia (2004)
In this paper, the dynamics of the free radical polymerization of methyl methacrylate (MMA) in a cooling jacketed continuous reactor were investigated. The modeling stage has been conducted regarding several underlying phenomena so to obtain the most accurate model as we can. Like most of the chemical processes, the mathematical model exhibits high interaction and nonlinearity. To control this system several methods can be implemented to control the system. However, the design of an efficient and reliable control strategy requires, in most cases, the linearization and decoupling of the model equations. In this first part of a paper series the process model is developed and validated prior to the implementation of a fuzzy control strategy.